Level of physical activity in chronic kidney patients and correlations with nutritional profile and quality of live (Revista Contexto & Saúde, 2023)
Studies have shown beneficial results for the practice of physical exercise in the adjuvant treatment of Chronic Kidney Disease (CKD). The aim of this study was to correlate the level of physical activity with the quality of life and nutritional profile of patients undergoing conservative treatment for CKD in a high complexity hospital. The sample consisted of patients of both sexes, aged over 18 years, undergoing conservative treatment for CKD and with a Glomerular Filtration Rate (GFR) lower than 89 mL/min/1.73m2. The social profile (gender, housing, marital status and education), health (pre-existing diseases, drinking behavior and tobacco) and nutritional profile (weight, height, Body Mass Index – BMI, Waist Circumference -WC and percentage fat – calculated from the triceps, subscapular and suprailiac skinfolds); level of physical activity and quality of life. The study included 70 patients with a mean age of 60.5 ± 9.57 years, 57.14% female, 52.85% diabetic and 80% hypertensive. For the nutritional profile, there was a high percentage of obesity (55.71%), high WC indices (95.04 ± 16.9 cm); and 67.15% had low levels of physical activity, with the highest average in domestic physical activities (32.23 min/week), being considered inactive. For the level of quality of life, lower scores in satisfaction with health (2.85 ± 1.53) and environment (2.73 ± 0.49); better scores in the psychological domain (3.73 ± 0.69) and social relationships (3.64 ± 0.73). The physically active group had lower values for weight (p=0.028), BMI (p=0.043) and WC (p=0.039) than the groups with low physical activity. The level of physical activity was positively correlated with GFR (r=0.190); fat percentage (r=0.004); fat mass (r=0.442); physical dimensions (r=0.212), general perception of health (r=0.125) and general satisfaction with health and quality of life (r=0.125); and with all dimensions of physical activity, namely: work (r=0.947), commuting (r=0.442), domestic (r=0.674) and leisure (r=0.564). Despite CKD being an inflammatory, chronic and progressive disease, with current pharmacological therapies proving to be limited in controlling its evolution, the study showed that physical activity can present a positive response in controlling parameters that contribute to its progression, being a positive path in the multidisciplinary care of the disease.
Keywords: Physical Activity; Quality of Life; Nutrition; Renal